A robot-assisted surgical system using a force-image control method for pedicle screw insertion. - Wei Tian; Xiaoguang Han; Bo Liu; Yajun Liu; Ying Hu; Xiao Han; Yunfeng Xu; Mingxing Fan; Haiyang Jin (PLoS ONE, 2014)
OBJECTIVE: To introduce a robot-assisted surgical system for spinal posterior fixation that can automatically recognize the drilling state and stop potential cortical penetration with force and image information and to further evaluate the accuracy and safety of the robot for sheep vertebra pedicle screw placement. METHODS: The Robotic Spinal Surgery System (RSSS) was composed of an optical tracking system, a navigation and planning system, and a surgical robot equipped with a 6-DOF force/torque sensor. The robot used the image message and force signals to sense the different operation states and to prevent potential cortical penetration in the pedicle screw insertion operation. To evaluate the accuracy and safety of the RSSS, 32 screw insertions were conducted. Furthermore, six trajectories were deliberately planned incorrectly to explore whether the robot could recognize the different drilling states and immediately prevent cortical penetration. RESULTS: All 32 pedicle screws were placed in the pedicle without any broken pedicle walls. Compared with the preoperative planning, the average deviations of the entry points in the axial and sagittal views were 0.50 ± 0.33 and 0.65 ± 0.40 mm, and the average deviations of the angles in the axial and sagittal views were 1.9 ± 0.82° and 1.48 ± 1.2°. The robot successfully recognized the different drilling states and prevented potential cortical penetration. In the deliberately incorrectly planned trajectory experiments, the robot successfully prevented the cortical penetration. CONCLUSION: These results verified the RSSS's accuracy and safety, which supported its potential use for the spinal surgery.